Cemented filling material and application thereof

By using a composite gelling system formed by anhydrous gypsum and cement in mine backfill to replace phosphorus tailings or phosphogypsum, the problems of insufficient compressive strength of the filling materials and environmental pollution are solved, and an efficient and environmentally friendly mine backfill effect is achieved.

CN119504221APending Publication Date: 2025-02-25HUBEI WANRUN NEW ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411734849.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing filling materials are insufficient in the backfilling of mines, and the use of phosphorus tailings and phosphogypsum has caused serious environmental pollution.

Method used

The compound gelling system formed by anhydrous gypsum and cement is used to replace phosphorus tailings or phosphorus gypsum. By controlling the mass ratio of cemented materials and aggregates, the amount of phosphorus tailings and phosphorus gypsum is reduced, and the compressive strength of cemented filling materials is improved.

Benefits of technology

It realizes high compressive strength of cemented filling materials, meets the strength requirements of mine filling, and reduces environmental pollution and complies with groundwater quality standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a cemented filling material and application thereof, and belongs to the technical field of filling materials, the cemented filling material comprises a cementing material, aggregate and water; the cementing material comprises cement and anhydrous gypsum; the aggregate comprises one or more of phosphogypsum, phosphate tailings and sandstone; the mass ratio of the cementing material to the aggregate is (2-6): (6-11), and the mass ratio of cement to anhydrite in the cementing material is 1: (1-11). The compound gel system formed by the anhydrous gypsum and the cement is used for replacing most of the phosphate tailings and the phosphogypsum, consumption of a large amount of the anhydrous gypsum can be achieved, the use amount of the phosphate tailings and the use amount of the phosphogypsum are reduced, and therefore environmental pollution is reduced, and meanwhile the prepared cemented filling material has the high compressive strength and is suitable for being used in a large scale. And the earth surface backfill standard requirements can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of filling materials, and in particular relates to a bonding filling material and application thereof. Background Art

[0002] With the continuous development of society, the importance of mineral resources to social economy has become increasingly prominent. With the large-scale and unlimited exploitation of mineral resources, there are a large number of mining voids underground, which not only damages the environment, but also has an irreversible impact on underground water veins, and also poses a certain threat to the surrounding safety.

[0003] Cementitious filling materials can be used to fill the mine pit after mining. The treatment methods currently used in mine goaf in my country are: direct landfill with waste ore near the mine; or use tailings from mineral processing, dry or wet backfill; or use various powdered industrial waste slag for dry or wet backfill; use cement as a cementing material and combine it with tailings or powdered industrial waste slag to make pulp, pump backfill, etc. Phosphate tailings are solid wastes left after phosphate ore is processed by mineral processing. They are low-grade phosphate ore. At the same time, with the increase of phosphate mining activities in various places, the tailings pollution generated by phosphate flotation is becoming more and more serious. Phosphogypsum is a solid waste generated in the wet phosphoric acid process. Its composition is relatively complex. In addition to calcium sulfate, there are also incompletely decomposed phosphate ore, residual phosphoric acid, fluoride, etc. At present, cement is generally used as a binder in combination with phosphate tailings or phosphogypsum for mine backfill or mine filling. However, the phosphorus content in phosphate tailings and phosphogypsum is relatively high. Using them for mine filling can easily cause eutrophication of the surrounding soil and water bodies, causing serious environmental pollution. At the same time, the compressive strength of the current cement, phosphate tailings or cement, phosphogypsum filling materials is relatively low and cannot meet the strength requirements after filling.

[0004] Therefore, there is an urgent need to develop a cementitious filling material that can meet the strength requirements and reduce environmental pollution. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application provides a bonding filling material and its application, aiming to solve the technical problems of insufficient strength of existing filling materials and serious environmental pollution.

[0006] In a first aspect, an embodiment of the present application provides a cementitious filling material, comprising a cementitious material, an aggregate and water; wherein the cementitious material comprises cement and anhydrous gypsum; the aggregate comprises one or more of phosphogypsum, phosphate tailings, and sand and gravel; the mass ratio of the cementitious material to the aggregate is (2~6):(6~11), and the mass ratio of cement to anhydrous gypsum in the cementitious material is 1:(1~11).

[0007] In the technical solution of the embodiment of the present application, a composite cementitious system formed by anhydrous gypsum and cement is used to replace phosphate tailings or phosphogypsum, which not only can realize the disposal of a large amount of anhydrous gypsum, but also reduces the amount of phosphate tailings and phosphogypsum. Anhydrous gypsum is a product of phosphogypsum after harmless treatment, and has a low phosphorus and fluorine content, which can ensure that the leachate water meets the groundwater quality standards (GBT 14848-2017) and reduce environmental pollution. At the same time, the prepared cementitious filling material has a high compressive strength, which can meet the filling strength requirements of the mine, thereby effectively solving the geological disaster problems caused by mining.

[0008] Among them, the anhydrous gypsum contained in the cementitious material can react with cement to form calcium aluminate to improve the strength of the prepared cementitious filling material. At the same time, the cementitious material containing cement and anhydrous gypsum is compounded with aggregates such as phosphate tailings and phosphogypsum, which not only solves the technical problem of eutrophication of water bodies caused by the large-scale use of phosphate tailings or phosphogypsum, but also the prepared cementitious filling material has good compressive strength after curing, which can meet the performance requirements of existing filling materials.

[0009] Furthermore, in the present application, the cementitious material and aggregate are controlled within a reasonable range, and the amount of cement and anhydrous gypsum in the cementitious material is controlled, so that the obtained cementitious filling material can meet the requirement of compressive strength>1.5MPa. Among them, if the amount of anhydrous gypsum is too low, the strength of the prepared cementitious filling material will be reduced; if the amount of anhydrous gypsum is too high, the incomplete hydration will cause the hardened body structure to be loose, which will further reduce the strength of the prepared cementitious filling material; if the amount of aggregate is too low, the strength of the prepared cementitious filling material will be reduced, and if the amount of aggregate is too high, the phosphorus content of the prepared cementitious filling material is high, which is easy to cause eutrophication of the surrounding soil and water.

[0010] In some embodiments, the aggregate includes phosphate tailings and sand and gravel, the mass ratio of the cementitious material, the phosphate tailings and the sand and gravel is (2-6): (0-4): 7, and the mass ratio of cement to anhydrous gypsum in the cementitious material is 1: (3-11).

[0011] In this embodiment, the cementitious filling material includes cementitious material, phosphate tailings and sand and gravel. By controlling the mass ratio of cementitious material, phosphate tailings and sand and gravel to (2~6):(0~4):7, and using a compound of phosphate tailings and sand and gravel to replace phosphate tailings, not only the introduction of phosphorus into the cementitious filling material is reduced, but also a cementitious filling material with higher compressive strength can be obtained.

[0012] In some embodiments, the mass ratio of the cementitious material, the phosphate tailings and the sand and gravel is (3-5):(1-3):7, and the mass ratio of cement to anhydrous gypsum in the cementitious material is 1:(5-9).

[0013] In this embodiment, by controlling the mass ratio of cementitious material, phosphate tailings and sand and gravel within the above range, and the mass ratio of cement to anhydrous gypsum is 1: (5-9), the prepared cementitious filling material can obtain better compressive strength.

[0014] In some embodiments, the cementitious filling material includes, by weight, 0.5 parts of cement, 4.5 parts of anhydrous gypsum, 1 part of phosphate tailings, and 7 parts of sand and gravel.

[0015] In this embodiment, by controlling the mass ratio of the cementitious material, the phosphate tailings and the sand and gravel to 5:1:7, and controlling the content of anhydrous gypsum in the cementitious material to 90%, the prepared cementitious filling material can obtain the best compressive strength.

[0016] In some embodiments, the aggregate is phosphogypsum, the mass ratio of the cementitious material to the phosphogypsum is (1-3):(3-5), and the mass ratio of cement to anhydrous gypsum in the cementitious material is 1:(1-5).

[0017] In this embodiment, the cementitious filling material includes a cementitious material and phosphogypsum. By controlling the mass ratio of cement, anhydrous gypsum and phosphogypsum within an appropriate range and using anhydrous gypsum to replace part of the phosphogypsum, not only the introduction of phosphorus into the cementitious filling material is reduced, but also the prepared cementitious filling material obtains a higher compressive strength.

[0018] In some embodiments, the mass ratio of the cementitious material to the phosphogypsum is (1-2):(4-5), and the mass ratio of cement to anhydrous gypsum in the cementitious material is 1:(1-3).

[0019] In this embodiment, by controlling the mass ratio of phosphogypsum and cementitious material to (1-2):(4-5), and controlling the mass ratio of anhydrous gypsum to cement to 1:(1-3), the prepared cementitious filling material can obtain better compressive strength.

[0020] In some embodiments, the cementitious filling material includes, by mass, 1 part of cement, 1 part of anhydrous gypsum, and 10 parts of phosphogypsum.

[0021] In this embodiment, by controlling the mass ratio of cement, anhydrous gypsum and phosphogypsum to 1:1:10, the prepared cementitious filling material can obtain better compressive strength.

[0022] In some embodiments, the cement is one or more of sulphoaluminate cement, silicate cement, and aluminate cement.

[0023] In this embodiment, cement and anhydrous gypsum are compounded to stimulate the anhydrous gypsum.

[0024] In some embodiments, the anhydrite is type II anhydrite with an average particle size of 50-100 μm.

[0025] In this embodiment, the particle size of anhydrous gypsum is controlled at 50-100 μm, so that the hardening speed and compressive strength of the cementitious filling material meet the requirements, and at the same time, it helps the cementitious filling material to form a uniform paste during slurrying, which facilitates the stability of the performance of the hardened body after construction.

[0026] In some embodiments, the particle size of phosphogypsum is 1-25 mm.

[0027] In this embodiment, by reasonably controlling the particle size of phosphogypsum, the flowability of the cementitious filling material can be improved, and the stratification and segregation of the prepared cementitious filling material can be avoided.

[0028] In some embodiments, the phosphate tailings are the whole tailings remaining after phosphate ore beneficiation, with an average particle size of 10 to 75 μm and a moisture content of less than 15%.

[0029] In this embodiment, by reasonably controlling the particle size of the phosphate tailings, it is helpful to improve the density and strength of the cementitious filling material; if the particle size of the phosphate tailings is too large, it is not conducive to forming a hardened body with uniform strength; and if the particle size of the phosphate tailings is too small, the specific surface area of ​​the cementitious filling material is large, thereby affecting the fluidity and stability of the slurry during filling construction. At the same time, if the water content of the phosphate tailings is too high, the compressive strength of the prepared cementitious filling material will be reduced.

[0030] In some embodiments, the sand and gravel are quartz sand and gravel or construction gravel with a particle size of 10-12 mm and a mud content of <5%.

[0031] In this embodiment, the particle size and mud content of the sand and gravel will affect the density and strength of the cementitious filling material. If the particle size of the sand and gravel is too large, the porosity of the filling body formed by the prepared cementitious filling material after construction will increase, thereby reducing the density and strength of the filling body formed after construction; and if the particle size of the sand and gravel is too small, the early strength of the filling body formed after construction will be affected due to insufficient interaction between the sand and gravel and the cementitious material. Understandably, if the mud content of the sand and gravel is too high, it will affect the workability of the prepared cementitious filling material, increase the porosity of the filling body formed after construction, and then reduce the compressive strength of the filling body formed after construction.

[0032] In some embodiments, the amount of water used is 20-55% of the total weight of the cementitious material and aggregate.

[0033] In this embodiment, by adjusting and optimizing the addition amount of cementitious filling material and water, the cementitious filling material has good fluidity and is easy to be transported to the area requiring filling through pipelines.

[0034] In the second aspect, the embodiment of the present application provides an application of the cementitious filling material as described in the first aspect in surface backfilling, comprising the following steps: filling the cementitious filling material into the surface goaf by pumping or gravity; the pH of the cementitious filling material is 8-9, the setting time is 14-21d, the overflow water solid content is less than 300ppm, the phosphorus and fluorine content is less than 0.1%, and the density of the filling body in the backfill area is 1.5-2.3t / m 3 , 28-day compressive strength > 1.5MPa.

[0035] In the technical solution of the embodiment of the present application, it is only necessary to backfill the cementitious filling material by pumping or gravity flow, and the process is simple. Surface backfill includes floor leveling of concave terrain under construction, surface backfill of open-pit mining, mine filling, etc. Among them, the pH of the cementitious filling material mainly affects the strength and bearing capacity of the filling body, and the cementitious filling material with a suitable setting time can ensure the smooth progress of construction. At the same time, the solid content and phosphorus and fluorine content of the overflow water will have an impact on the environment. Excessive solid content of the overflow water means that more aggregate particles are not effectively settled. If it is discharged directly, it will cause pollution to surface water and groundwater and affect the water quality. Furthermore, the density of the filling body in the backfill area is 1.5-2.3t / m 3 , which helps to improve the stability and strength of the filling body. The 28-day compressive strength is greater than 1.5MPa, which can repair the surface well. Compared with cement, the solidified body has higher strength, more uniform filling, and no stratification.

[0036] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION

[0037] The following embodiments of the technical solution of the present application will be described in detail in conjunction with the embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned embodiment descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0039] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0040] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0041] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0042] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0043] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the embodiments, and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.

[0044] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0045] The existing technology usually uses a mixture of phosphate tailings or phosphogypsum and cement for backfilling the surface (such as mine goafs and mine shaft goafs). However, the amount of phosphate tailings or phosphogypsum is large, and their high phosphorus content can easily cause soil eutrophication and water resource pollution. In addition, the strength of the formed cementing body is insufficient, which affects the filling effect.

[0046] In order to solve the problem that existing filling materials are insufficient in strength and easily cause environmental pollution, the present application provides a cementitious filling material and its application, wherein, by adopting a cementitious filling material with good compressive strength and low content of phosphate tailings and phosphogypsum, it can meet the surface backfill standard requirements and reduce environmental pollution.

[0047] In a first aspect, an embodiment of the present application provides a cementitious filling material, comprising a cementitious material, an aggregate and water; wherein the cementitious material comprises cement and anhydrous gypsum; the aggregate comprises one or more of phosphogypsum, phosphate tailings, and sand and gravel; the mass ratio of the cementitious material to the aggregate is (2~6):(6~11), and the mass ratio of cement to anhydrous gypsum in the cementitious material is 1:(1~11).

[0048] In the technical solution of the embodiment of the present application, the composite cementitious system formed by anhydrous gypsum and cement replaces phosphate tailings or phosphogypsum, which not only realizes the disposal of a large amount of anhydrous gypsum, but also reduces the amount of phosphate tailings and phosphogypsum, reducing environmental pollution; at the same time, the prepared cementitious filling material has a high compressive strength, which can meet the filling strength requirements of the mine, thereby effectively solving the geological disaster problem caused by mining. Among them, the anhydrous gypsum contained in the cementitious material can react with cement to form calcium aluminate to improve the strength of the prepared cementitious filling material. At the same time, the cementitious material containing cement and anhydrous gypsum is compounded with aggregates such as phosphate tailings and phosphogypsum, which not only solves the technical problem of eutrophication of water bodies caused by the large-scale use of phosphate tailings or phosphogypsum, but also the prepared cementitious filling material has good compressive strength after solidification, which can meet the performance requirements of existing filling materials.

[0049] Specifically, in the embodiment of the present application, the cementitious material and aggregate are controlled within a reasonable range, and the amount of cement and anhydrous gypsum in the cementitious material is controlled, so that the obtained cementitious filling material can meet the requirement of compressive strength>1.5MPa. Among them, if the amount of anhydrous gypsum is too low, the strength of the prepared cementitious filling material will be reduced; if the amount of anhydrous gypsum is too high, the incomplete hydration will cause the hardened body structure to be loose, which will further reduce the strength of the prepared cementitious filling material; if the amount of aggregate is too low, the strength of the prepared cementitious filling material will be reduced, and if the amount of aggregate is too high, the phosphorus content of the prepared cementitious filling material is high, which is easy to cause eutrophication of the surrounding soil and water.

[0050] Specifically, the mass ratio of the cementitious material to the aggregate can be 2:6, 2:7, 2:10, 2:11, 5:6, 5:7, 5:11, 6:7, 6:10, 6:11 or other ratios within the above range, and the mass ratio of cement to anhydrous gypsum in the cementitious material can be 1:1, 1:2, 1:4, 1:6, 1:7, 1:10, 1:11 or other ratios within the above range.

[0051] Furthermore, in some embodiments, the aggregate includes phosphate tailings and sand and gravel, the mass ratio of the cementitious material, the phosphate tailings and the sand and gravel is (2-6): (0-4): 7, and the mass ratio of cement to anhydrous gypsum in the cementitious material is 1: (3-11).

[0052] In the technical solution of the embodiment of the present application, the cementitious filling material includes cementitious material, phosphate tailings and sand and gravel. By controlling the mass ratio of cementitious material, phosphate tailings and sand and gravel to (2~6):(0~4):7, and using a compound of phosphate tailings and sand and gravel to replace phosphate tailings, not only the introduction of phosphorus into the cementitious filling material is reduced, but also a cementitious filling material with higher compressive strength can be obtained.

[0053] Specifically, the mass ratio of the cementitious material, phosphate tailings and sand and gravel can be 2:0:7, 2:3:7, 2:4:7, 3:0:7, 3:1:7, 3:2:7, 3:4:7, 4:0:7, 4:2:7, 4:4:7, 5:0:7, 5:2:7, 5:4:7, 6:0:7, 6:4:7 or other ratios within the above range, and the mass ratio of cement to anhydrous gypsum in the cementitious material can be 1:3, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11 or other ratios within the above range.

[0054] Furthermore, in some embodiments, the mass ratio of the cementitious material, the phosphate tailings and the sand and gravel is (3-5):(1-3):7, and the mass ratio of cement to anhydrous gypsum in the cementitious material is 1:(5-9).

[0055] In the technical solution of the embodiment of the present application, by controlling the mass ratio of cementitious material, phosphate tailings and sand and gravel within the above range, and the mass ratio of cement to anhydrous gypsum is 1: (5~9), the prepared cementitious filling material can obtain better compressive strength.

[0056] Specifically, the mass ratio of cementitious material, phosphate tailings and sand and gravel can be 3:1:7, 3:2:7, 3:3:7, 4:1:7, 4:2:7, 4:3:7, 5:1:7, 5:2:7, 5:3:7 or other ratios within the above range, and the mass ratio of cement to anhydrous gypsum in the cementitious material can be 1:5, 1:6, 1:7, 1:8, 1:9 or other ratios within the above range.

[0057] Furthermore, in some embodiments, the cementitious filling material includes, by weight, 0.5 parts of cement, 4.5 parts of anhydrous gypsum, 1 part of phosphate tailings, and 7 parts of sand and gravel.

[0058] In the technical solution of the embodiment of the present application, by controlling the mass ratio of cementitious material, phosphate tailings and sand and gravel to 5:1:7, and controlling the content of anhydrous gypsum in the cementitious material to 90%, the prepared cementitious filling material can obtain the best compressive strength.

[0059] Furthermore, in some embodiments, the aggregate is phosphogypsum, the mass ratio of the cementitious material to the phosphogypsum is (1-3):(3-5), and the mass ratio of cement to anhydrous gypsum in the cementitious material is 1:(1-5).

[0060] In the technical solution of the embodiment of the present application, the binder material includes cementitious material and phosphogypsum. By controlling the mass ratio of cement, anhydrous gypsum and phosphogypsum within an appropriate range and using anhydrous gypsum to replace part of the phosphogypsum, not only the introduction of phosphorus into the binder filling material is reduced, but also the prepared binder filling material obtains a higher compressive strength.

[0061] Specifically, the mass ratio of the cementitious material to the phosphogypsum can be 1:3, 1:4, 1:5, 2:3, 2:4, 2:5, 3:3, 3:4, 3:5 or other ratios within the above range, and the mass ratio of cement to anhydrous gypsum in the cementitious material can be 1:1, 1:2, 1:3, 1:4, 1:5 or other ratios within the above range.

[0062] Furthermore, in some embodiments, the mass ratio of the cementitious material to the phosphogypsum is (1-2):(4-5), and the mass ratio of cement to anhydrous gypsum in the cementitious material is 1:(1-3).

[0063] In the technical solution of the embodiment of the present application, by controlling the mass ratio of cementitious material and phosphogypsum to (1~2):(4~5), and controlling the mass ratio of cement and anhydrous gypsum to 1:(1~3), the prepared cementitious filling material can obtain better compressive strength.

[0064] Specifically, the mass ratio of cementitious material to phosphogypsum can be 1:4, 1:5, 2:4, 2:5 or other ratios within the above range, and the mass ratio of cement to anhydrous gypsum can be 1:1, 1:2, 1:3 or other ratios within the above range.

[0065] Furthermore, in some embodiments, the cementitious filling material includes, by mass, 1 part of cement, 1 part of anhydrous gypsum, and 10 parts of phosphogypsum.

[0066] In the technical solution of the embodiment of the present application, by controlling the mass ratio of cement, anhydrous gypsum and phosphogypsum to 1:1:10, the prepared cementitious filling material can obtain better compressive strength.

[0067] Furthermore, in some embodiments, the cement is one or more of sulphoaluminate cement, silicate cement, and aluminate cement.

[0068] In the technical solution of the embodiment of the present application, cement and anhydrous gypsum are compounded to stimulate the anhydrous gypsum, preferably silicate cement.

[0069] Furthermore, in some embodiments, the anhydrite is type II anhydrite with an average particle size of 50-100 μm.

[0070] In the technical solution of the embodiment of the present application, the particle size of anhydrous gypsum is controlled at 50~100μm, so that the hardening speed and compressive strength of the prepared cementitious filling material meet the requirements, and at the same time help the cementitious filling material to form a uniform paste during slurrying, which facilitates the stability of the performance of the hardened body after construction.

[0071] Furthermore, in some embodiments, the particle size of phosphogypsum is 1-25 mm.

[0072] In the technical solution of the embodiment of the present application, by reasonably controlling the particle size of phosphogypsum, the flow properties of the cementitious filling material can be improved and the stratification and segregation of the cementitious filling material can be avoided.

[0073] Furthermore, in some embodiments, the phosphate tailings are the whole tailings remaining after phosphate ore beneficiation, with an average particle size of 10 to 75 μm and a moisture content of less than 15%.

[0074] In the technical solution of the embodiment of the present application, by reasonably controlling the particle size of the phosphate tailings, it is helpful to improve the density and strength of the prepared cementitious filling material; if the particle size of the phosphate tailings is too large, it is not conducive to forming a hardened body with uniform strength; and if the particle size of the phosphate tailings is too small, the specific surface area of ​​the cementitious filling material is large, thereby affecting the fluidity and stability of the slurry during filling construction. Understandably, if the water content of the phosphate tailings is too high, the compressive strength of the prepared cementitious filling material will be reduced.

[0075] Furthermore, in some embodiments, the sand and gravel are quartz sand and gravel or construction gravel, with a particle size of 10-12 mm and a mud content of <5%.

[0076] In the technical solution of the embodiment of the present application, the particle size and mud content of the sand and gravel will affect the density and strength of the cementitious filling material. If the particle size of the sand and gravel is too large, the porosity of the filling body formed by the prepared cementitious filling material after construction will increase, thereby reducing the density and strength of the filling body formed after construction. If the particle size of the sand and gravel is too small, the early strength of the filling body formed after construction will be affected due to insufficient interaction between the sand and gravel and the cementitious material. If the mud content of the sand and gravel is too high, it will affect the workability of the prepared cementitious filling material, increase the porosity of the filling body formed after construction, and then reduce the compressive strength of the filling body formed after construction.

[0077] Furthermore, in some embodiments, the amount of water used is 20-55% of the total mass of the cementitious material and the aggregate.

[0078] In the technical solution of the embodiment of the present application, by adjusting and optimizing the amount of cementitious filling material and water added, the cementitious filling material has good fluidity, which is convenient for transportation through pipelines or self-flow to the area that needs to be filled.

[0079] In the second aspect, the embodiment of the present application provides an application of the cementitious filling material as described in the first aspect in surface backfilling, comprising the following steps: filling the cementitious filling material into the surface goaf by pumping or gravity; the pH of the cementitious filling material is 8-9, the setting time is 14-21d, the overflow water solid content is less than 300ppm, the phosphorus and fluorine content is less than 0.1%, and the density of the filling body in the backfill area is 1.5-2.3t / m 3 , 28-day compressive strength > 1.5MPa.

[0080] In the technical solution of the embodiment of the present application, it is only necessary to backfill the cementitious filling material by pumping or self-flowing, and the process is simple. Surface backfilling includes floor leveling of concave terrain under construction, surface backfilling of open-pit mining, mine filling, etc. Among them, the pH of the cementitious filling material mainly affects the strength and bearing capacity of the filling body. If the pH is too high, it will affect the coagulation and hardening process of the cementitious filling material, thereby affecting the strength development of the filling body, while if the pH is too low, it will destroy the crystal structure inside the cementitious filling material, resulting in a decrease in the bearing capacity of the solidified body. The cementitious filling material at a suitable coagulation time can ensure the smooth progress of the construction. If the coagulation time is too long, the construction efficiency will be reduced. If the coagulation time is too short, it is not conducive to pumping or self-flowing, and the construction difficulty will be increased. At the same time, the solid content and phosphorus and fluorine content of the overflow water will have an impact on the environment. If the solid content of the overflow water is too high, it means that more aggregate particles are not effectively settled. If it is discharged directly, it will pollute the surface water and groundwater and affect the water quality. Furthermore, the density of the solidified body in the backfill area is 1.5-2.3 t / m 3, which helps to improve the stability and strength of the filling body. The 28-day compressive strength is greater than 1.5MPa, which can repair the surface well. Compared with cement, the solidified body has higher strength, more uniform filling, and no stratification.

[0081] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0082] The following examples are used in the following raw materials: Cement: 325 cement, commercially available; Anhydrous gypsum: average particle size is 50~100μm; Phosphogypsum: average particle size is 1~25mm; Phosphate tailings: The whole tailings left after phosphate ore dressing, with an average particle size of 10~75μm, a moisture content of <15%, and main components of CaO 32.61%, SiO 2 2.26%, MgO 18.82%, P 2 O 5 3.64%, Fe 2 O 3 1.19%, Al 2 O 3 0.25%, MnO 2 0.13%, CO 2 30.33%, others 8.77%; Sand and gravel: gravel for construction, with particle size of 10~12mm and mud content of less than 5%.

[0083] 1. Preparation method Example 1 133 g of cement, 133 g of anhydrous gypsum and 1330 g of phosphogypsum were mixed uniformly to obtain a mixture. 479 mL of water was added to the mixture and mixed uniformly to obtain a cementitious filling material.

[0084] Among them, the cementitious material is 266g and the aggregate is 1330g. The mass ratio of the cementitious material to the aggregate is 2:10, and the mass ratio of the cement in the cementitious material to the anhydrous gypsum is 1:1.

[0085] Example 2 133 g of cement, 399 g of anhydrous gypsum and 1064 g of phosphogypsum were mixed uniformly to obtain a mixture. 575 mL of water was added to the mixture and mixed uniformly to obtain a cementitious filling material.

[0086] Among them, the cementitious material is 532g and the aggregate is 1064g. The mass ratio of the cementitious material to the aggregate is 5:10, and the mass ratio of the cement in the cementitious material to the anhydrous gypsum is 1:3.

[0087] Example 3 133 g of cement, 665 g of anhydrous gypsum and 798 g of phosphogypsum were mixed uniformly to obtain a mixture. 670 mL of water was added to the mixture and mixed uniformly to obtain a cementitious filling material.

[0088] Among them, the cementitious material is 798g and the aggregate is 798g. The mass ratio of the cementitious material to the aggregate is 10:10, and the mass ratio of the cement in the cementitious material to the anhydrous gypsum is 1:5.

[0089] Example 4 96 g of cement, 288 g of anhydrous gypsum, 768 g of phosphate tailings and 1346 g of sand and gravel were mixed evenly to obtain a mixture. 550 mL of water was added to the mixture and mixed evenly to obtain a cementitious filling material.

[0090] Among them, the cementitious material is 384g and the aggregate is 2114g. The mass ratio of the cementitious material to the aggregate is 2:11, and the mass ratio of the cement in the cementitious material to the anhydrous gypsum is 1:3.

[0091] Example 5 96 g of cement, 480 g of anhydrous gypsum, 576 g of phosphate tailings and 1346 g of sand and gravel were mixed evenly to obtain a mixture. 575 mL of water was added to the mixture and mixed evenly to obtain a cementitious filling material.

[0092] Among them, the cementitious material is 576g and the aggregate is 1922g. The mass ratio of the cementitious material to the aggregate is 3:10, and the mass ratio of the cement in the cementitious material to the anhydrous gypsum is 1:5.

[0093] Example 6 96 g of cement, 672 g of anhydrous gypsum, 384 g of phosphate tailings and 1346 g of sand and gravel were mixed evenly to obtain a mixture. 600 mL of water was added to the mixture and mixed evenly to obtain a cementitious filling material.

[0094] Among them, the cementitious material is 768g and the aggregate is 1730g. The mass ratio of the cementitious material to the aggregate is 4:9, and the mass ratio of the cement in the cementitious material to the anhydrous gypsum is 1:7.

[0095] Example 7 96 g of cement, 864 g of anhydrous gypsum, 192 g of phosphate tailings and 1346 g of sand and gravel were mixed evenly to obtain a mixture. 625 mL of water was added to the mixture and mixed evenly to obtain a cementitious filling material.

[0096] Among them, the cementitious material is 960g and the aggregate is 1538g. The mass ratio of the cementitious material to the aggregate is 5:8, and the mass ratio of the cement in the cementitious material to the anhydrous gypsum is 1:9.

[0097] Example 8 96 g of cement, 1056 g of anhydrous gypsum and 1346 g of sand and gravel were mixed evenly to obtain a mixture. 650 mL of water was added to the mixture and mixed evenly to obtain a cementitious filling material.

[0098] Among them, the total amount of cementitious material is 1152g, the total amount of aggregate is 1346g, the mass ratio of cementitious material to aggregate is 6:7, and the mass ratio of cement in the cementitious material to anhydrous gypsum is 1:11.

[0099] Comparative Example 1 133 g of cement, 931 g of anhydrous gypsum and 532 g of phosphogypsum were mixed uniformly to obtain a mixture. 830 mL of water was added to the mixture and mixed uniformly to obtain a cementitious filling material.

[0100] Among them, the total amount of cementitious material is 1064g, the total amount of aggregate is 532g, the mass ratio of cementitious material to aggregate is 10:5, and the mass ratio of cement in the cementitious material to anhydrous gypsum is 1:7.

[0101] Comparative Example 2 192 g of cement, 960 g of phosphate tailings and 1346 g of sand and gravel were mixed evenly to obtain a mixture. 625 mL of water was added to the mixture and mixed evenly to obtain a cementitious filling material.

[0102] Among them, the cementitious material is 192g and the aggregate is 2306g. The mass ratio of the cementitious material to the aggregate is 1:12, and the mass ratio of the cement in the cementitious material to the anhydrous gypsum is 1:0.

[0103] Comparative Example 3 96 g of cement, 1056 g of phosphate tailings and 1346 g of sand and gravel were mixed evenly to obtain a mixture. 625 mL of water was added to the mixture and mixed evenly to obtain a cementitious filling material.

[0104] Among them, there are 96g of cementitious materials and 2402g of aggregates, and the mass ratio of cementitious materials to aggregates is 0.5:12.5.

[0105] Comparative Example 4 96 g of cement, 96 g of anhydrous gypsum, 960 g of phosphate tailings and 1346 g of sand and gravel were mixed evenly to obtain a mixture. 625 mL of water was added to the mixture and mixed evenly to obtain a cementitious filling material.

[0106] Among them, the cementitious material is 192g and the aggregate is 2306g. The mass ratio of the cementitious material to the aggregate is 1:12, and the mass ratio of the cement in the cementitious material to the anhydrous gypsum is 0.5:0.5.

[0107] 2. Test Method pH: Use a pH meter to directly test the filling slurry.

[0108] Setting time: refer to "Standard for Test Methods for Basic Properties of Building Mortar" (JGJ 70-2009).

[0109] Strength and density of filling body, solid content of overflow water, and phosphorus and fluorine content: The cementitious filling materials of the above-mentioned Examples 1-8 and Comparative Examples 1-4 were injected into a 7×7×7 mold and cured at 90% humidity and 20°C for 28 days. After that, the solidified body was subjected to uniaxial compressive strength test at a loading rate of 0.05 KN / s in a 300 KN-grade press, and the phosphorus and fluorine content and solid content in the leaching solution, as well as the density of the solidified body were tested.

[0110] III. Analysis of test results of various embodiments and comparative examples Table 1 Composition and performance test data of cementitious filling materials of Examples 1 to 3 and Comparative Example 1

[0111] Table 2 Composition and performance test data of cementitious filling materials of Examples 4 to 8 and Comparative Examples 2 to 4

[0112] As can be seen from Table 1, the present invention uses a composite gelling system formed by anhydrous gypsum and cement to replace phosphogypsum, and can obtain a filling material that meets the strength requirements, which not only consumes a large amount of anhydrous gypsum, but also avoids the problem of environmental pollution caused by the large-scale use of phosphogypsum. At the same time, it can be seen from the comparison between Comparative Example 1 and Example 1 that the amount of anhydrous gypsum is sufficient, but when the amount of phosphogypsum is too small, the strength decreases due to the low aggregate component, and the strength requirements cannot be met.

[0113] Further, as shown in Table 2, the cementitious filling material of the present invention uses anhydrous gypsum as the main component of cementitious material, which can react with cement to generate calcium sulfonate to improve strength, and uses it and sandstone to replace phosphate tailings, which not only reduces the problem of eutrophication of water bodies caused by the large-scale use of phosphate tailings in the filling material, but also the prepared cementitious filling material has good compressive strength after solidification, meeting the requirement that the filling material is greater than 1.5MPa. Compared with Example 7, it can be seen that although the content of phosphate tailings increases, anhydrous gypsum is not added to the cementitious material, and the compressive strength is significantly reduced, indicating that anhydrous gypsum can form calcium sulfonate with cement to improve strength, and anhydrous gypsum can be used to replace phosphate tailings to obtain a cementitious filling material that meets the strength requirements. Compared with Example 7, although the content of phosphate tailings aggregate increases in Comparative Example 4, the content of anhydrous gypsum in the cementitious system is insufficient, and a higher strength cementitious filling material cannot be obtained.

[0114] In addition, it can be seen from Tables 1 and 2 that the pH value of the cementitious filling material provided by the present invention is 8-9, which will not destroy the internal crystal structure of the material, thereby making the filling body have good bearing capacity; the setting time is 14-21d, which can ensure the smooth progress of construction during the filling process; the overflow water solid content is <300ppm, indicating that the filling material in the slurry can be effectively settled and has a high material utilization rate; the phosphorus and fluorine content is <0.1%, and the heavy metal ion concentration complies with the "Groundwater Quality Standards" and will not cause environmental pollution.

[0115] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A cementing filling material, characterized in that: It comprises a cementitious material, an aggregate and water; wherein the cementitious material comprises cement and anhydrous gypsum; the aggregate comprises one or more of phosphogypsum, phosphate tailings and sand and gravel; the mass ratio of the cementitious material to the aggregate is (2-6):(6-11), and the mass ratio of cement to anhydrous gypsum in the cementitious material is 1:(1-11).

2. The cementitious filling material according to claim 1, characterized in that: The aggregate includes phosphate tailings and sand and gravel, the mass ratio of the cementitious material, the phosphate tailings and the sand and gravel is (2-6): (0-4): 7, and the mass ratio of cement to anhydrous gypsum in the cementitious material is 1: (3-11).

3. The cementitious filling material according to claim 2, characterized in that: The mass ratio of the cementitious material, phosphate tailings and sand and gravel is (3-5): (1-3): 7, and the mass ratio of cement to anhydrous gypsum in the cementitious material is 1: (5-9).

4. The cementitious filling material according to claim 3, characterized in that: Calculated by mass, it includes 0.5 parts of cement, 4.5 parts of anhydrous gypsum, 1 part of phosphate tailings, and 7 parts of sand and gravel.

5. The cementitious filling material according to claim 1, characterized in that: The aggregate is phosphogypsum, the mass ratio of the cementitious material to the phosphogypsum is (1-3):(3-5), and the mass ratio of cement to anhydrous gypsum in the cementitious material is 1:(1-5).

6. The cementitious filling material according to claim 5, characterized in that: The mass ratio of the cementitious material to the phosphogypsum is (1-2):(4-5), and the mass ratio of cement to anhydrous gypsum in the cementitious material is 1:(1-3).

7. The cementitious filling material according to claim 6, characterized in that: Calculated by mass, it includes 1 part of cement, 1 part of anhydrous gypsum and 10 parts of phosphogypsum.

8. The cementitious filling material according to claim 1, characterized in that: The cement is one or more of sulphoaluminate cement, silicate cement and aluminate cement; and / or The anhydrous gypsum is type II anhydrous gypsum with an average particle size of 50-100 μm; and / or The particle size of the phosphogypsum is 1 to 25 mm; and / or The phosphate tailings are the whole tailings remaining after phosphate ore dressing, with an average particle size of 10-75 μm and a moisture content of less than 15%; and / or The sand and gravel are quartz sand and gravel or construction gravel with a particle size of 10-12 mm and a mud content of <5%.

9. The cementitious filling material according to claim 1, characterized in that: The amount of water used is 20-55% of the total mass of the cementitious material and the aggregate.

10. Use of the cementitious filling material according to any one of claims 1 to 9 in surface backfilling, characterized in that: The following steps are involved: The cementing filling material is filled into the surface goaf by pumping or gravity flow; the pH of the cementing filling material is 8-9, the setting time is 14-21 days, the overflow water solid content is less than 300ppm, the phosphorus and fluorine content is less than 0.1%, and the density of the backfill area filling body is 1.5-2.3t / m 3 , 28-day compressive strength > 1.5MPa.

Citation Information

Cited By

  • Anhydrous gypsum-based mine filling mortar

    CN122325204A